2020
DOI: 10.3390/foods9050659
|View full text |Cite
|
Sign up to set email alerts
|

Association between Breast Milk Mineral Content and Maternal Adherence to Healthy Dietary Patterns in Spain: A Transversal Study

Abstract: The composition of breast milk is influenced by many factors, some of which dependent on the mother and others on the child. Changes in lactation and other factors depending on the mother’s physiology and anthropometric characteristics, as well as her nutritional status and diet, are of key importance. Breast milk minerals have been extensively studied with highly uneven results. In this work, a comparison will made with data across the world. To understand the factors that might explain the disparity, several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 74 publications
3
20
0
1
Order By: Relevance
“…For example, colostrum has a different concentration of macronutrients, micronutrients and bioactive components than that found in milk at one month of lactation, when milk is considered to be mature in terms of composition [ 55 ]. However, breast milk is not a static fluid, and it continues to evolve after this period, as may its bacterial communities [ 5 , 6 ]. In this sense, some studies have shown conflicting results regarding bacteria levels comparing colostrum with other moments of lactation [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, colostrum has a different concentration of macronutrients, micronutrients and bioactive components than that found in milk at one month of lactation, when milk is considered to be mature in terms of composition [ 55 ]. However, breast milk is not a static fluid, and it continues to evolve after this period, as may its bacterial communities [ 5 , 6 ]. In this sense, some studies have shown conflicting results regarding bacteria levels comparing colostrum with other moments of lactation [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Breastfeeding grants protection against diarrhoea, necrotising enterocolitis, respiratory infections, and atopic dermatitis, and decreases the risk of non-communicable diseases, including type 2 diabetes mellitus, overweight, and obesity, and it is closely related to low rates of infant mortality [ 1 , 2 , 3 ]. This extraordinary maternal fluid contains a wide range of essential nutrients and different bioactive components such as proteins, oligosaccharides, minerals, lipids, vitamins, immune factors, microRNAs, and hormones, which altogether explain its important health benefits for the infant [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under 6 months of age, no indications are given regarding the intake of sodium, as breast milk is considered the gold standard for all nutrients and, therefore, also for sodium. The sodium content of breast milk differs according to the mother’s geographical origin and her weight status, suggesting an important role in maternal eating habits [ 17 ]. However, it must be emphasized that the sodium content in breast milk is low (17 mg/100 mL) [ 18 ] and, based on this amount, breastmilk substitutes have been created, whereas cow’s milk has a sodium content about three times that of human milk.…”
Section: Recommendations For Dietary Salt and Sugar Intake In Chilmentioning
confidence: 99%
“…These studies have not evaluated dietary sources of Pb from combinations of diverse foods and nutrients because some dietary nutrients (e.g., iron) can interfere with the intestinal absorption of Pb(Shah- Kulkarni, et al 2016). Dietary pattern analysis has recently been developed to investigate comprehensive dietary links with health (Sanchez, et al 2020, Shi 2020) to better represent nutritional exposures and re ect daily eating habits.…”
Section: Introductionmentioning
confidence: 99%